Development of scientific requirements for climate-neutral buildings and sustainable funding schemes in Germany - Sylvi Eckart; Juliane Jäger; Nicolas Kerz; Andreas Rietz (Acta Polytechnica CTU Proceedings, 2022)
The German Climate Protection Plan 2050 describes interim targets and measures for the implementation of the Paris Climate Agreement, including the building sector. With the “New European Bauhaus”, the EU Commission has currently initiated an ambitious process. While new construction has been in the foreground up to now, the existing building stock must make a significant contribution to achieving the climate protection goals in the future. Robust building technology and a high degree of adaptability lead to a longer useful life and are thus more sustainable, both economically and in terms of ecological balance. Resilience to the consequences of climate change is gaining in importance. The main goal of this contribution is to inform about the latest developments in governmental policies and subsidy schemes. As part of the National Climate Protection Programme 2030, the new “Federal Funding for Efficient Buildings (BEG)” was introduced in 2021. Research projects investigated how, with the introduction of efficiency house classes, funding can take greater account of the life cycle approach and other aspects of sustainability. At the same time, general and special requirements for the ecological, socio-cultural and economic quality were developed as a supplement to the existing certification systems and introduced by the Federal Building Ministry as “Quality Seal for Sustainable Buildings” (QNG).